Age at natural menopause genetic risk score in relation to age at natural menopause and primary open-angle glaucoma in a US-based sample. Issue 2 (February 2017) - Pasquale, Louis R.; Aschard, Hugues; Kang, Jae H.; Bailey, Jessica N. Cooke; Lindström, Sara; Chasman, Daniel I.; Christen, William G.; Allingham, R. Rand; Ashley-Koch, Allison; Lee, Richard K.; Moroi, Sayoko E.; Brilliant, Murray H.; et al.
Abstract: Objective: Several attributes of female reproductive history, including age at natural menopause (ANM), have been related to primary open-angle glaucoma (POAG). We assembled 18 previously reported common genetic variants that predict ANM to determine their association with ANM or POAG. Methods: Using data from the Nurses' Health Study (7, 143 women), we validated the ANM weighted genetic risk score in relation to self-reported ANM. Subsequently, to assess the relation with POAG, we used data from 2, 160 female POAG cases and 29, 110 controls in the National Eye Institute Glaucoma Human Genetics Collaboration Heritable Overall Operational Database (NEIGHBORHOOD), which consists of 8 datasets with imputed genotypes to 5.6+ million markers. Associations with POAG were assessed in each dataset, and site-specific results were meta-analyzed using the inverse weighted variance method. Results: The genetic risk score was associated with self-reported ANM ( P = 2.2 × 10 –77 ) and predicted 4.8% of the variance in ANM. The ANM genetic risk score was not associated with POAG (Odds Ratio (OR) = 1.002; 95% Confidence Interval (CI): 0.998, 1.007; P = 0.28). No single genetic variant in the panel achieved nominal association with POAG ( P ≥0.20). Compared to the middle 80 percent, there was also no association with the lowest 10 th percentile or highest 90 th percentile of genetic risk score with POAG (OR = 0.75; 95% CI: 0.47, 1.21; P = 0.23 and OR = 1.10; 95% CI: 0.72, 1.69; P = 0.65, respectively). Conclusions: A genetic risk score predicting 4.8% of ANM variation was not related to POAG; thus, genetic determinants of ANM are unlikely to explain the previously reported association between the two phenotypes. Abstract : Supplemental Digital Content is available in the text